2018
DOI: 10.1002/lno.10797
|View full text |Cite
|
Sign up to set email alerts
|

Shallow ponds are biogeochemically distinct habitats in salt marsh ecosystems

Abstract: Runaway expansion of shallow ponds can catalyze the conversion of vegetated marshes into open water environments. Predicting how this transition affects ecosystem functioning is difficult because little is known about pond biogeochemistry. We characterized sediment organic matter sources and transformations in three ponds with different plant communities, over alternating periods of tidal isolation and flushing, during summer and fall, using a combination of stable isotopes, lipid biomarkers, and benthic fluxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
55
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(64 citation statements)
references
References 119 publications
(342 reference statements)
9
55
0
Order By: Relevance
“…Sulfide concentrations were low, even at their peak, despite abundant sulfate availability and consecutive hours of low DO. This hints that sulfur is rapidly recycled, until the ponds become anoxic, which is consistent with sediment flux measurements (Spivak et al, 2018), pore water dynamics (Rigaud et al, 2018), and the presence of active sulfate reducing and sulfur oxidizing bacterial communities (Kearns et al, 2017;Rao et al, 2016;Salman et al, 2015;Wilbanks et al, 2014). For instance, the activity of bacteria in the orders Desulfobacterales and Chromatiales, which include members of the pink berry consortia, changed over diel cycles in a nearby PIE pond (Kearns et al, 2017).…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 72%
See 1 more Smart Citation
“…Sulfide concentrations were low, even at their peak, despite abundant sulfate availability and consecutive hours of low DO. This hints that sulfur is rapidly recycled, until the ponds become anoxic, which is consistent with sediment flux measurements (Spivak et al, 2018), pore water dynamics (Rigaud et al, 2018), and the presence of active sulfate reducing and sulfur oxidizing bacterial communities (Kearns et al, 2017;Rao et al, 2016;Salman et al, 2015;Wilbanks et al, 2014). For instance, the activity of bacteria in the orders Desulfobacterales and Chromatiales, which include members of the pink berry consortia, changed over diel cycles in a nearby PIE pond (Kearns et al, 2017).…”
Section: Journal Of Geophysical Research: Biogeosciencessupporting
confidence: 72%
“…Diel changes in surface water chemistry were measured over two summer days (25 and 26 July 2016) in Ponds 1 and 4. We focused on these ponds because we had previously characterized primary producer communities, metabolism rates, and organic matter dynamics over tidal stages and seasons (Spivak et al, 2017(Spivak et al, , 2018.…”
Section: Diel Changes In Pond Surface Water Chemistrymentioning
confidence: 99%
“…The sediment therefore fulfills an important function in the tidal ponds as a CO 2 reservoir for the benthic primary production as the water column was almost devoid of CO 2 in the afternoon (Figure 4). This supports previous observations from deeper tidal ponds in the same marshes, where Spivak et al (2018) found a significant DIC efflux from the sediment to the water.…”
Section: Ph and Cosupporting
confidence: 93%
“…We infer that ebullition is driven by photosynthesis in this setting (see section 3.4), rather than methanogenesis. Methanogenesis should be strongly limited by high rates of sulfate reduction that occur in this pond (Spivak et al, ). Therefore E was evaluated over a large range of possible bubble sizes and initial enrichment of O 2 ; these parameters control the initial concentration and evolution of Ne in an O 2 ‐enriched bubble (Ne b ).…”
Section: Resultsmentioning
confidence: 99%
“…The study location was a salt marsh pond in the Plum Island Ecosystems Long Term Ecological Research site in Massachusetts, USA (42.7411°N, 70.8309°W), and has been previously described in Spivak et al (, ). The pond was circular, covered 7,000 m 2 , and had 25 cm mean depth during the study period.…”
Section: Methodsmentioning
confidence: 99%